STRENGTH FITNESS AS A KEY TO HEALTHY PHYSICAL ACTIVITY AMONG UKRAINIAN YOUTH - Shkolа , Olena; Gukov , Mykita (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines the importance of strength fitness as one of the key factors in promoting a healthy lifestyle among Ukrainian youth. The purpose of this study is to determine the impact of strength fitness on the level of physical activity and health among Ukrainian youth. The research analyzed the dynamics of physical indicators in university students who regularly engage in strength fitness training. The results demonstrate a positive influence of strength workouts on endurance, muscular strength, energy levels, and general well–being. It analyzes the impact of strength training on physical development, motor activity, and the psycho–emotional state of young people. The advantages of regular strength exercise are highlighted in the context of preventing hypodynamia and maintaining overall health. It has been proven that integrating regular strength fitness activities into youth lifestyles helps reduce physical inactivity and promotes the development of a healthy lifestyle.